Geopolymer Concrete: A Review of Development and Opportunities - Lloyd, Natalie; Rangan, B. Vijaya (CI-Premier Pte Ltd, 2010)
Geopolymer results from the reaction of a source material that is rich in silica and alumina with alkaline liquid. It is essentially cement free concrete. This material is being studied extensively and shows promise as a greener substitute for ordinary Portland cement concrete in some applications. Research is shifting from the chemistry domain to engineering applications and commercial production of geopolymer concrete. It has been found that geopolymer concrete has good engineering properties with a reduced global warming potential resulting from the total replacement of ordinary Portland cement. The research undertaken at Curtin University of Technology has included studies on geopolymer concrete mix design, structural behavior and durability. This paper presents the results from studies on mix design development to enhance workability and strength of geopolymer concrete. The influence of factors such as, curing temperature and regime, aggregate shape, strengths, moisture content, preparation and grading, on workability and strength are presented. The paper also included brief details of some recent applications of geopolymer concrete.